The use and perceived value of electronic health information resources by health care professionals in the field of medicine, pharmacy, and nursing in Jazan province, Saudi Arabia - Saad S. Alqahtani; Santhosh Joseph Menachery; Renju Ravi; Tahir Hakami; Manal Almalki (Elsevier, 2024)
Background: Healthcare workers increasingly use Electronic Health Information Resources (EHIRs) to make evidence-based decisions. Our study was intended to assess the perception, attitude, and practice of healthcare professionals in medicine, pharmacy, and nursing regarding their perceived value and use of EHIRs. Methods: We conducted an observational cross-sectional study using a pre-validated questionnaire among healthcare professionals in Jazan province from September 2022 to February 2023. We included healthcare professionals and interns with medical, pharmacy, or nursing degrees and excluded those who refused informed consent. Results: We included fully completed data from 294 participants, with an actual response rate of just 80.1 %. Almost 87.41 % utilized the health information resources at their workplace, with UpToDate [39.45 %] and Medscape [67.01 %] being the most frequently used medical databases. The health facilities' access to electronic health resources significantly impacted healthcare professionals' [p = 0.04] and medical interns' [p = 0.02] roles. Faculty members felt the need to access electronic health information at their workplace [p = 0.00]. Lack of time to access electronic health information due to a busy schedule was a significant reason that impacted the attitude of medical professionals [p = 0.008] and nursing staff [p = 0.025]. An excessive amount of clinically unrelated data was the primary obstacle (181/294, p < 0.0001) in using electronic health information resources. Conclusion: Our study showed the pattern of healthcare professionals using EHIRs in the Jazan province, Saudi Arabia. We believe the study's outcome can help increase the calibre of electronic health information services available to healthcare professionals and raise awareness of different EHIRs in improving clinical care.